Report of the Study Group on Agricultural Strategies Eastern Region of India - Planning Commission (Planning Commission, 1985)
The study on Agricultural Strategies for the Eastern Region of India highlights the significant productivity gaps in states like Bihar, Uttar Pradesh, West Bengal, Orissa, Assam, and eastern Madhya Pradesh. Despite considerable agricultural potential, these regions underperform due to water management issues, untapped groundwater, limited access to high-yield variety (HYV) seeds, fertilizer shortages, and inadequate infrastructure. Wheat and rice yields are particularly affected by soil salinity, alkalinity, and uneven irrigation coverage. The report recommends comprehensive interventions, including improved irrigation and drainage, soil amelioration, increased supply of certified seeds and fertilizers, strengthened agricultural extension services, and enhanced cooperative and institutional support for farmers. Strategic investments in infrastructure, technology adoption, and equitable resource distribution are emphasized to boost productivity, reduce regional disparities, and promote a self-reliant agricultural ecosystem in Eastern India.
Government of India Planning Commission July 1985
Government of India Planning Commission
Keywords: Eastern Region; Agricultural Productivity; Irrigation; High-Yield Varieties; Wheat; Rice; Water Management; Soil Improvement; Infrastructure; Farmer Extension Services; Cooperative Strengthening; Fertilizer Access